Assessment method for forest landscapes based on aesthetic attributes as explanatory variables of preferences - Zubelzu, Sergio; Hernández, Ana (Instituto de Ecología, A.C., 2015)
this paper presents an assessment method for forest landscapes based on a mixed approach using aesthetics attributes. A set of variables have been deduced in order to objectively quantify in photographs its lines, colors, shapes, texture, scale and spatial composition. Referred variables have been measured in a forest landscape and preferences for that landscape have been collected. Using this information, regression functions have been tested to deduce a predictive method for preferences. The deduced optimum method adopts a linear structure and is able to explain 60,1% of the variance of population preferences.